An international multi-stakeholder delphi consensus exercise to develop a core outcomes set (COS) for surgical fixation of rib fractures. Issue 2 (February 2020) - Ingoe, Helen M.A.; Eardley, William; Rangan, Amar; Hewitt, Catherine; McDaid, Catriona
Highlights: A core outcome set developed for rib fracture surgery trials involving international stakeholders. Multiple expert stakeholder panels including medical, allied health professionals and patients. Delphi consensus process using approved methods used by the Core Outcome Measures in Effectiveness Trials (COMET) Group. Outcomes gathered by way of systematic review and suggestions by consensus panel members. Consensus concluded on a 23 core outcome set following three rounds of anonymous online Delphi questionnaires. Abstract: Introduction: A patient-relevant, focused Core Outcome Set (COS) is essential to the design of clinical trials dealing with chest wall trauma, in order to maximise quality of evidence regarding impact of interventions and to reduce research waste. Methods: Outcome measures were collated by way of systematic review and entered into a three round Delphi consensus completed anonymously online. Participants were international clinicians and allied health professionals (AHP) involved in the treatment of rib fractures as well as patients who had experienced severe chest trauma. Consensus thresholds for statements were defined a priori as a group rating of more than 70% or less than 15% for 'important' or 'not important'. Results: Sixty-five participants responded to the first round and the final round Final round consisted of five AHP, two patients and 16 clinicians from eight different countries. Twenty-three outcomes were regarded as important for the COS; eight adverse events, three mortality, five clinical or physiological outcomes, six life impact and one resource-related. Health related quality of life was rated highest of the life impact outcomes but participants thought it was also important to assess disability, physical function, quality of life, return to activities and return to work. Conclusion: Collecting serious adverse outcomes was important to all stakeholders as were life impact outcomes such as quality of life, physical function and return to activities. Resource use outcomes were considered less important. We recommend this Core Outcome Set, developed with multiple relevant stakeholders, for use in future clinical trials, following further work on the most appropriate methods and instruments for measurement.